Brain renaissance : from Vesalius to contemporary neuroscience - Catani, Marco; Sandrone, Stefano (Oxford University Press, 2015)
Brain Renaissance, from Vesalius to contemporary neuroscience is published on the 500th anniversary of the birth and the 450th anniversary of the death of Vesalius. The authors translated those Latin chapters of the Fabrica dedicated to the brain, a milestone in the history of neuroscience. Many chapters are accompanied by a commentary tracking the discoveries that paved the way to our modern understanding of the brain - from the pineal gland that regulates sleep, the fornix and mammillary bodies for memory, the colliculi for auditory and visual perception, and the cerebellum for motor control.